Effect of the lateral wall valgisation in the treatment of patients with endocrine orbitopathy - Krause, Matthias; Halama, Dirk; Gladilin, Evgeny; Kauder, Birgit; Neuhaus, Michael-Tobias; Sander, Anna K.; Lethaus, Bernd; Zimmerer, Rüdiger (The British journal of oral & maxillofacial surgery, 2023)
Orbital decompression is an established procedure used to correct exophthalmos that results from excess orbital soft tissue. This study aimed to explore a new minimally-invasive technique that features three-dimensional planning and patient-specific implants for lateral valgisation (LAVA) of the orbital wall. We analysed the outcomes of this procedure in nine endocrine orbitopathy (EO) patients (32-65 years of age with a mean clinical activity score of 4.3) who underwent this procedure between 2021 and 2022, including seven patients diagnosed with dysthyroid optic neuropathy. The impact of LAVA and wall resection on orbital areas, volumes, Hertel values, visual acuity, and new-onset diplopia was determined. Among our results, we found that LAVA and resection of 18 orbital walls resulted in significant enlargement of the orbital volume from a preoperative mean of 30.8 ± 3.5 cm3 to a mean of 37.3 ± 5.8 cm3 postoperatively (mean difference, 6.2 ± 1.8 cm3; p < 0.001); this procedure also resulted in a significant reduction in the mean Hertel value, from 28.7 ± 1.9 mm to 20.0 ± 1.9 mm (mean difference, 8.7 ± 1.9 mm; p < 0.001). The procedure resulted in visual acuity declined in three patients (33.3 %) with reductions from 0.25 to 0.125, 0.8 to 0.125, and 1.2 to 0.7, respectively. No new diplopia occurred postoperatively, however, our study included five patients with preoperative diplopia that did not improve postoperatively and required additional surgical intervention. Similarly, four patients required supplemental eyelid surgery. In conclusion, our study suggests the effects of the LAVA with the partial floor resection seems to be effective, which provides a substantially improved outcome for patients undergoing surgical treatment of EO via the use of double navigation and piezosurgical methods.
Online verfügbar 16. Dezember 2022, Artikelversion 2. März 2023
Gesehen am 20.04.2023